Generalization of Comparative Growth Properties of Entire Functions of Two Complex Variables Related to Relative Order - Balram Prajapati; Anupma Rastogi (International Journal of Mathematics And its Applications, 2016)
In this paper we study some results related to comparative growth properties of entire functions of two complex variables on the basis of relative order and relative lower order of entire functions of two complex variables.